On Self-Interest and Greed - Gebhard Kirchgässner (Center for Research in Economics, Management and the Arts (CREMA), 2014)
First the assumption of self-interest as applied in Economics is presented. Here we also discuss areas in which (many) people behave less self- but more other-regarding than traditional economic models assume. Then, greedy behaviour is considered as existing in the political and economic world . Here we refer to corruption as well as to the role of money as a positional good. We also discuss such behaviour in the academic world, in which money plays a role as well as reputation. Thus, while the assumption of mutually disinterested rationality is a very powerful instrument for analysing individual behaviour, to explain some phenomena we have to recognise that people are not only sometimes other-regarding, but also sometimes greedy, and that they might value money much more than traditional Economics assumes. We conclude with some remarks on what we can learn in this respect from Behavioural Economics.
Keywords: B41; 330; Economic Model of Behaviour; Self-Interest; Altruism; Greed; Corruption